GST fraud: unveiling the truth - Othman, Zaleha; Nordin, Fareez Fahmy; Bidin, Zainol; Mansor, M., (ExcelingTech Publishers, 2019)
Goods and services tax (GST) fraud is increasing in Malaysia, resulting in the loss of income for the government. Although there are mechanisms in place to prevent GST fraud, fraudsters are smart and will usually find ways of outwitting such measures.To combat such fraud, it is essential to understand the types of GST fraud perpetrated. Therefore, the purpose of this qualitative study was to identify types of GST fraud in Malaysia. Using a case study approach, the study found six major forms of GST fraud: falsifying claims, sales manipulation, nonsubmission of GST forms, failure to register, GST avoidance and carousel fraud. Notably, there are commonalities between GST fraud in Malaysia and in other developed and developing countries. This study suggests that authorities should be alert and aggressive in preventing GST fraud. The research contributes to tax administration and the development of literature by demonstrating the impact of a new tax policy with respect to indirect taxation such as GST to facilitate fraud prevention measures.